RESPONSE TO REFUGE ISSUES IN INDONESIAN IMMIGRATION LENS IN IMMIGRATION DETENTION HOUSES - Hana Farah Dhiba; Wahyu Eka Putra (Polteknik Imigrasi, 2021)
The phenomenon of refugees is one of the topics of discussion in the international world. This situation was triggered by the increasing number of refugees scattered in various countries around the world. The existence of refugees is often a special concern for countries that are both transit places and destinations. In Indonesia, tens of thousands of refugees and asylum seekers stop and live. Some of the Arab and African countries and ethnic Rohingya who are hit by armed conflict and acute poverty. They lived for years while waiting for a third country. Their existence is increasingly causing various problems in society. The research uses normative legal research methods with 7 approaches. From the research results, it can be concluded that the presence of refugees in Indonesia has been going on for decades. The refugees entered by land and sea routes to Indonesian territory. Various policies have been taken to deal with the presence of refugees from abroad, one of which is Presidential Regulation Number 125 of 2016 concerning Policies for Handling Refugees from Abroad. However, over time, the refugee status intersected with the status of illegal immigrants contained in the regulation of the Director General of Immigration. This in the future raises various problems related to the handling of refugees in Indonesia.